2022
DOI: 10.1080/13573322.2022.2099369
|View full text |Cite
|
Sign up to set email alerts
|

‘I play on a club team': examining the development of the physically active habitus in early primary education

Abstract: The drop off in physical activity (PA) for children has led to an increased focus on their PA engagement, due to the poor health outcomes often linked to this decline. Subsequently, stakeholders, across a variety of fields, have problematised and intervened in activity settings to address this decline. Many of these studies acknowledge high levels of activity in the primary years and tend to prioritise their efforts on the adolescent years. An important limitation in these studies is that they greatly overlook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As for the role played by PE, several authors [ 29 , 30 ] express that this discipline is permeated by male and female stereotypes that are present at school, validating the differences between genders and thus affecting school culture. In this sense, Cameron and Humbert [ 32 ] indicated that this situation is closely related to the roles played by men and women in society, concretely representing this through the existing differentiation between sports designated as “male” or “female.” In this way, gendered differences in PE and incidental physical activity (play) at school become naturalized to educators [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for the role played by PE, several authors [ 29 , 30 ] express that this discipline is permeated by male and female stereotypes that are present at school, validating the differences between genders and thus affecting school culture. In this sense, Cameron and Humbert [ 32 ] indicated that this situation is closely related to the roles played by men and women in society, concretely representing this through the existing differentiation between sports designated as “male” or “female.” In this way, gendered differences in PE and incidental physical activity (play) at school become naturalized to educators [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in our tests of the personal characteristic's effects on PH, three basic models were tested: an associative two-factor unspecified LGCM, a hierarchical factor-of-curves LGCM, and a hierarchical curve-offactors LGCM before or after controlling for gender, self-evaluate healthy condition (SEHC), self-evaluate family social economic status (SEFSES), and weekly time spent on physical activities (WTSPA). Evidence of various perceived influence covariance, in either of these ways, would provide further justifications and a possible explanation for enabling some students, and restricting others, in physical activity participation (Chan et al, 2020;Smee et al, 2022). On this background, we will address the following questions:…”
Section: Introductionmentioning
confidence: 99%
“…The PH thus connects with multiple types of social capitals that are intertwined with each other—such as perceived influences from families, perceived influences from physical education in schools, and perceived influences from communities—which may directly or indirectly mold participants’ PH. In addition, the PH connecting the sport field and capital is expressed through the body in a way that responds to other agents in the field automatically and with predictability ( Dukic et al, 2017 ; Smee et al, 2022 ). Given the above perspective, the PH also embodies the generative function of capital and a materialized form in terms of participants’ dispositions, which are desired indications to be looked for and quantified by physical education educators and health-promoting researchers ( Strandbu et al, 2020 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%